Internet-Based Flipbook as A Health Education Medium on The Dangers of Smoking for Teenagers - Marsiana Wibowo; Ahmad Ahid Mudayana; Nurulita Priandini (Gaster, 2023)
A strategy to decrease smoking prevalence in Indonesia is to conduct health education. Various health education media have been widely developed and published, but there has not been found a flipbook educational media with the theme of adolescent smoking control this study aimed to identify the effectiveness of internet-based flipbook media in changing adolescents' knowledge and attitudes about the dangers of smoking. This research is a pre-experimental design of the type one group pretest-posttest. Researchers treated the youth group using an internet-based flipbook on adolescents' knowledge and attitudes. The results obtained that the Wilcoxon test results on the knowledge variable produced a 2-tailed sig value of 0.0 and the pairT-Testest on the attitude variable is 0.000 at a 2-tailed sig value. The flipbook used for this intervention has proven effective in changing adolescents' knowledge and attitudes about the dangers of smoking.